Données sur l’écologie et la productive des espèces de cystoseira de la Mer Noire - Vasiliu, Florian (Cercetări Marine - Recherches Marines, 2026)
The present paper describes some peculiarities that have concern with Cystoseira genera along the Romanian sea shore. Ecological conditions of the areas populated by these seaweeds, the pronounced trend of them quantitative diminishing, as well as datum on Cystoseira barbata productivity are presented. An original procedure for primary productivity determination is described, too.